Model Distribusi Salinitas dan Temperatur Air Laut dengan Menggunakan Metode Numerik 2D di Muara Sungai Toaya dan Muara Sungai Palu - Rahman, Abd.; Arfiah, Arfiah; Mudin, Yutdam (Gravitasi, 2017)
The research on salinity and temperature distribution in Palu Bay waters has been conducted. This study aims to models the salinity and temperature suitable distribution caused by river discharge and current patterns using wind and tidal generators. This area of research covers estuary of Palu River and estuary of Toaya River. Research stages use primary data of river flow, river salinity and temporary river temperature. For secondary data use bathymetry data, tidal data and wind data. The results showed that the pattern of surface currents in the waters of Palu Bay is very weak. The maximum current velocity at the time of the farm and full moon in the mouth of Palu Bay are 0.15 m/s 0.1 m/s. The salinity value of the estuary of the Palu River and the estuary of the Toaya River at the time of install is 6.8‰ and 32.4‰ while at low tide is 5.2‰ and 9.4‰. The estuary of the Palu River estuary and the mouth of the Toaya River at tides of 26.4 °C and 27.9 °C while at low tide is 26.3 °C and 27.7 °C. Key words: Current pattern, Salinity distribution, Temperature distribution